Infectious Disease Informatics Syndromic Surveillance for Public Health and BioDefense - Chen, Hsinchun; Zeng, Daniel; Yan, Ping.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Computer-based infectious disease surveillance systems are capable of real-time or near real-time detection of serious illnesses and potential bioterrorism agent exposures and represent a major step forward in disease surveillance. Infectious Disease Informatics: Syndromic Surveillance for Public Health and Bio-Defense is an in-depth monograph that analyzes and evaluates the outbreak modeling and detection capabilities of existing surveillance systems under a unified framework, and presents the first book-length coverage of the subject from an informatics-driven perspective. Individual chapters consider the state of the art, including the facilitation of data collection, sharing and transmission; a focus on various outbreak detection methods; data visualization and information dissemination issues; and system assessment and other policy issues. Eight chapters then report on several real-world case studies, summarizing and comparing eight syndromic surveillance systems, including those that have been adopted by many public health agencies (e.g., RODS and BioSense). The book concludes with a discussion of critical issues and challenges, with a look to future directions. This book is an excellent source of current information for researchers in public health and IT. Government public health officials and private-sector practitioners in both public health and IT will find the most up-to-date information available, and students from a variety of disciplines, including public health, biostatistics, information systems, computer science, and public administration and policy will get a comprehensive look at the concepts, techniques, and practices of syndromic surveillance.
SYNDROMIC SURVEILLANCE SYSTEMS -- Infectious Disease Informatics: An Introduction and An Analysis Framework -- Public Health Syndromic Surveillance Systems -- Syndromic Surveillance Data Sources and Collection Strategies -- Data Analysis and Outbreak Detection -- Data Visualization, Information Dissemination, and Alerting -- System Assessment and Evaluation -- SYNDROMIC SURVEILLANCE SYSTEM CASE STUDIES -- BioSense -- RODS -- BioPortal -- ESSENCE -- New York City Syndromic Surveillance Systems -- EARS -- Argus -- HealthMap -- Challenges and Future Directions.
Keywords: Medicine; Public health; Medical records -- Data processing; Epidemiology; Information systems; Management information systems; Medicine & Public Health; Health Informatics; Public Health; Business Information Systems; e-Commerce/e-business.; Information Systems and Communication Service; Epidemiology